A didática da história nos videogames: “God of war” e suas dimensões frente à cultura histórica - Morais, Hugo Albuquerque de (2017)
The present dissertation has an objective to analyse the historical culture in the Playstation videogame series “God of War”, investigating aspects concerning its visual culture and plot. Inspired by Greek mythology, the piece presents a gamma of elements that show an insight into the past. Besides that , even though a product linked to entertainment, but, as it has become a meaningful form of cultural expression, it goes far beyond this initial purpose. The concept of didactics of history established by the historian Jörn Rüsen becomes essential within the debate, because from it we can realize these historical dimensions within the game, being this one a historical source. For more, the dissertation tries to understand the dialogical movement that the piece , besides peculiarities of its language. The vídeogames were created in the late 50’s, since then, has gradually become a very popular product in the global market, moreover, they are forms of contemporary artistic experimentation.This is the sense in which we intend to analize the electronic game series, considering it as a contemporary artistic experimentation that is understood from a representation of the past.